Pseudomonas aeruginosa Expressing Vitreoscilla Hemoglobin Shows Increased Production of L-Lysine ?-Oxidase: an Enzyme used in Cancer Therapy - Kahraman, Hüseyin (Fırat University, 2018)
L-lysine ?-oxidase (LO) is one of a few microbial enzymes with therapeutic potential in certain cancers. The enzyme has been determined in several bacteria and fungi. Its production is mainly regulated by carbon sources and oxygen. . Thus, the aim of this study was to determine the nutritional requirements and effect of oxygen concentration on the production of LO in P. aeruginosa, and in their recombinants using a highly efficient oxygen uptake system, the Vitreoscilla hemoglobin. This study concerns the effect of a higher oxygen uptake provided by a recombinant system, the Vitreoscilla hemoglobin, on the production of LO in Pseudomonas aeruginosa. The results showed that the recombinant bacterium expressing Vitreoscilla hemoglobin gene (vgb) had distinct L-lysine activity from the host strain under both carbon catabolite repression and no repression conditions. In a rich medium supplemented with glucose, the recombinant strain showed 20-40 % higher L-lysine activity than the host strain. This difference was even more significant in the medium with no glucose supplement, where the recombinant strain showed almost 2-fold higher enzyme activity throughout the incubation. The results sometime were contradictory in terms of the effect of carbon source (mainly glucose) and oxygen on the production of this enzyme.